Analisis Penerapan Prinsip Good Corporate Governance pada Bank Syariah Indonesia - Ameliyani, Rizki; Arsyad, Kamaruddin; Possumah, Bayu Taufiq; Majid, Jamaluddin; Wawo, Andi (Tangible Journal, 2025)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles at Bank Syariah Indonesia (BSI) during the 2021-2024 period. GCG plays a vital role in maintaining customer trust, strengthening institutional stability, and ensuring operational compliance with maqashid syariah values such as justice (al-‘adl), welfare (al-maslahah), and trustworthiness (hifz al-mal). This research employs a qualitative descriptive method using a content analysis approach based on BSI’s annual reports from 2021 to 2024. The results show that BSI has implemented GCG principles very well and consistently, with an average disclosure rate of 90.55%, categorized as “Excellent.” However, two indicators multiple directorships and legal case resolution still require improvement, with an average of 87.5%. These findings indicate that BSI has applied a governance system that is transparent, accountable, and fair, while also reflecting maqashid syariah principles in upholding trust and promoting public welfare.